Clinical and functional outcome of total transanal endorectal pull-through procedure for the management of Hirschsprung's disease - Aisha Masoud Al Shukairi; Madhavan Nayar; Mahmood Masud Al Awfi (SpringerOpen, 2024)
Abstract Objective The aim of the study is to evaluate the complications and long-term bowel function in Hirschsprung's disease (HD) patients following total transanal endorectal pull-through (TERPT) surgery operated in a tertiary hospital in Oman. Methods A retrospective data retrieval was done for patients diagnosed with Hirschsprung's disease and underwent total transanal endorectal pull-through procedure during the period from December 2008 to June 2019 with concomitant prospective phone call questionnaire interview to assess the long-term functional outcome of children aged 3 years and older. Results Total transanal endorectal pull-through was performed in 61 patients. The mean age at the time of operation was 7.71 ± 8.26 months. The most common late complication was anal excoriation (19.7%). Of the patients, 61.5% had a normal to fair score, and the remaining 38% had a poor score in their functional outcome questionnaire. The majority had no social problems (65.4%), while 15.4% had problems causing varying degrees of social restrictions. Conclusion The short-term outcomes of total transanal endorectal pull-through are found to be acceptable. In addition, the long-term functional outcome post total transanal endorectal pull-through was found to be satisfactory; however, longer follow-up studies with larger sample sizes are needed for more accurate functional outcome evaluation.